Багатовимірний статистичний аналіз стану підприємництва в регіонах України - Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Hanna; Власюк, Ю. О. (My University, 2019)
UK: В статті запропоновано систему показників для характеристики стану підприємництва та проведено статистичний аналіз сучасного стану підприємництва в регіонах на основі багатокритеріальної оцінки, а саме кластер ний аналіз. По одержаних кластерах регіонів виконане рейтингове оцінювання кластерів регіонів за обраними показниками с узагальненням їх позиції за допомогою суми місць. EN: The article proposes a system of indicators for the characterization of the entrepreneurship condition. For the monitoring and assessment of the entrepreneurship condition in the regions, were used the available data from the State Statistics Service concerning the subjects of entrepreneurship, in particular enterprises, including small and individual entrepreneurs. The assessment of the state of e entrepreneurship condition in the regions proposed to conduct on the basis of estimated specific indicators that characterize the density of economic entities, the attraction of labour and costs on workforce, sales volumes and financial results of activity. The statistical analysis of the current entrepreneurship condition in the regions on the basis of multicriteria assessment, namely cluster analysis was conducted. For the classification of regions according to the obtained indicators, the algorithm of the k-medium method, which belongs to the group of reference type iterative methods, was used. The decision on the number of clusters was taken on the basis of the previous hierarchical clusterization, for which were used the Ward method and the Euclidean distance. The dendrogram of business similarity of the regions of Ukraine has shown that it is expedient to allocate six clusters, in which with the help of РР STATISTICA were calculated the average indicators of the state of entrepreneurship. According to the obtained clusters of regions, the rating of clusters of regions according to selected indicators was carried out with the generalization of their position using the sum of places.
Multilateral statistical analysis of entrepreneurship condition in the regions of Ukraine
Keywords: підприємництво; регіони; кластерний аналіз; рейтинг; entrepreneurship; regions; cluster analysis; rating